Deficient Suppression of Default Mode Regions during Working Memory in Individuals with Early Psychosis and at Clinical High-Risk for Psychosis - Fryer, Susanna L.; Woods, Scott W.; Kiehl, Kent A.; Calhoun, Vince D.; Pearlson, Godfrey; Roach, Brian J.; Ford, Judith M.; Srihari, Vinod H.; McGlashan, Thomas H.; Mathalon, Daniel H. (Frontiers in Psychiatry, 2013)
Background: The default mode network (DMN) is a set of brain regions typically activated at rest and suppressed during extrinsic cognition. Schizophrenia has been associated with deficient DMN suppression, though the extent to which DMN dysfunction predates psychosis onset is unclear. This study examined DMN suppression during working memory (WM) performance in youth at clinical high-risk (CHR) for psychosis, early schizophrenia patients (ESZ), and healthy controls (HC). We hypothesized that the DMN would show load-dependent suppression during WM retrieval in HC but not in ESZ, with CHR participants showing an intermediate pattern. Methods: FMRI data were collected from CHR (n=32), ESZ (n=22), and HC (n=54) participants, ages 12-30. DMN regions were defined via seed-based connectivity analysis of resting state fMRI data from an independent HC sample. Load-dependent deactivations of these DMN regions in response to WM probes were interrogated. Results: HC showed linear load-dependent increases in DMN deactivation. Significant Group-by-Load interactions were observed in DMN regions including medial prefrontal and lateral posterior parietal cortices. Group-by-Load effects in posterior DMN nodes resulted from less suppression at higher WM loads in ESZ relative to HC, with CHR differing from neither group. In medial prefrontal cortex, suppression of activity at higher WM loads was significantly diminished in both CHR and ESZ groups, relative to HC. In addition, investigation of dorsolateral prefrontal (DLPFC) activations revealed that ESZ activated right DLPFC significantly more than HC, with CHR differing from neither group. Conclusion: While HC showed WM load-dependent modulation of DMN suppression, CHR individuals had deficient higher-load DMN suppression that was similar to, but less pronounced than, the distributed suppression deficits evident in ESZ patients. These results suggest that DMN dysregulation associated with schizophrenia predates psychosis onset